COMPETITIVE INTELLIGENCE IMPACT IN THE GROWTH OF FRANCHISING NETWORKS - SANTOS, DEBORAH OLIVEIRA; ASSIS, LILIAN BAMBIRRA; SANTOS, CHRISTOPH AUGUSTO OLIVEIRA (Journal of Sustainable Competitive Intelligence, 2020)
This paper endeavored to identify how the competitive intelligence process influences the growth and performance of franchise networks. The research employed a qualitative method and the field work was done with 15 franchisors from different sectors of activity. Two data analysis techniques were utilized: discourse analysis and critical incident technique. As a result, five critical incidents were found, that is, five competitive intelligence processes which would lead to the growth of a franchise network. In addition, three direct effects on performance were discussed: 1) increase sales and revenues; 2) increase the number of franchise units; 3) boosts chances of survival and growth of the network in local and external markets. On the other hand, it was possible to notice the existence of a dissonance between the perception of the franchisors regarding the rigor and structure of competitive intelligence process in the multiple franchise networks in the market.